2010
DOI: 10.17305/bjbms.2010.2649
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Left Ventricular Remodelling in Kidney Transplant Recipents in the First Posttransplant Year

Abstract: Cardiovascular diseases (CVD) are a major cause of morbidity and leading cause of mortality in almost 50% of patients (pts) with chronic kidney disease (CKD), including kidney transplant recipients. Left ventricular hypertrophy (LVH) is the most common structural alteration and powerful risk factor for cardiovascular complications in the uremic patients. The aim of this study is to analyze predictors of the left ventricular remodelling in the first year after kidney transplantation based on comparison of echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…In one study, the percentage of patients with LVH shown on echocardiography declined after the first post‐transplant year from 67% to 37%, confirming the positive relationship between LVH and the elimination of uremia‐related risk factors after successful renal transplantation …”
Section: Kidney Transplant As Treatment For Uremic Cardiomyopathymentioning
confidence: 91%
“…In one study, the percentage of patients with LVH shown on echocardiography declined after the first post‐transplant year from 67% to 37%, confirming the positive relationship between LVH and the elimination of uremia‐related risk factors after successful renal transplantation …”
Section: Kidney Transplant As Treatment For Uremic Cardiomyopathymentioning
confidence: 91%
“…Dzemidzić et al have shown that renal transplantation dramatically reduces the proportion of patients with LVH from 67% to 37% with correlations in improved creatinine clearance and in reduction of the serum creatinine values; as well as values of parathyroid hormone. 105 Additionally, Wali et al have shown that 70% of patients with a baseline LVEF <40% prior to renal transplantation, recovered at follow-up at 6 months with LVEF >50% on ventriculography-gated blood pool. Normalization of LVEF was associated with improvement in NYHA class and was the only significant factor associated with reduced hazard for CCF hospitalization and death (RR 0.90).…”
Section: Managementmentioning
confidence: 99%
“…Wali et al ( 6 ) Kidney transplantation in ESRD patients with advanced systolic heart failure resulted in an increase in LVEF and improved the functional status of congestive heart failure (CHF). Dzemidzic et al ( 18 ) showed that before transplantation, 67% of patients had echocardiographic signs of LVH that after first post-transplant year, 37% of patients remained with LVH (40% reduced). Several studies ( 11 , 14 , 16 , 19 ) reported that after kidney transplantation, there was a reduction of the LVH respect to the pre-transplant dialytic status.…”
Section: Discussionmentioning
confidence: 99%